RV mass measurement at end‐systole: Improved accuracy, Reproducibility, and reduced segmentation time. Issue 5 (31st March 2015) - Altmayer, Stephan P.L.; Teeuwen, Laurens A.; Gorman, Robert C.; Han, Yuchi
<x xml:space="preserve">Abstract</x> Purpose To evaluate the accuracy, reproducibility, and contouring time of RV mass in end‐systole (ES) and end‐diastole (ED). Magnetic resonance imaging (MRI) has been shown to be accurate and reproducible for the evaluation of right ventricular (RV) volume and function. RV mass, assessed in end‐diastolic (ED) phase, is one of the least reproducible variables. The choice of end‐systolic (ES) phase could offer an alternative to improve reproducibility, since the selection of the basal slice and the visualization of the usually thin RV wall are easier in this phase. Materials and Methods To evaluate accuracy, 11 sheep were imaged in vivo and their RV free walls were weighed after removing epicardial fat. To evaluate reproducibility, 30 normal subjects and 30 subjects with pulmonary arterial hypertension (PAH) were imaged and interobserver and intraobserver variabilities were assessed in the ES and the ED. Segmentation time was recorded after visual selection of ES and ED phases. Results ES RV mass measurement has less absolute variability (5.2% ± 3.2) compared to ED (10.6% ± 6.3) using weighed RV mass in sheep as the gold standard (P < 0.001). ES segmentation yielded higher intraobserver (intraclass correlation coefficients [ICC] = 0.94–0.99; coefficient of variability [CoV] = 6–7.3%) and interobserver (ICC = 0.85–0.98; CoV = 10.9–11.7%) reproducibility than ED segmentation. Segmentation time in humans was 25–28% faster in ES (P < 0.001). Conclusion The MRI assessment of RV mass is more accurate, reproducible, and faster in the ES phase. J. Magn. Reson. Imaging 2015;42:1291–1296.